Editorial: Gendered Cultures in Platform Economies—Entertainment, Expertise, and Online Selfhood - Panos Kompatsiaris; Cláudia Álvares; Sofie Van Bauwel (Media and Communication, 2025)
This thematic issue examines the gendered dimensions of platform economies, focusing on the construction of gendered online selfhood. Through the affordances of social media platforms, users expand the range of topics and content accessible to the public, simultaneously exposing these subjects to increased visibility and potential debate. Platforms such as TikTok, YouTube, Instagram, Twitch, X, and Telegram enable anyone to create channels and publicize content on virtually any topic, fostering niche communities. In other words, platforms, driven by their pursuit of attention, time, and data, cannot be analyzed solely through a business or organizational lens. The economic dimension is intertwined with cultural formations—beliefs, values, and identity constructions—which carry an anthropological dimension. In this thematic issue, we are particularly interested in the gendered aspects of this intertwining.